2001
DOI: 10.2113/gscanmin.39.2.557
|View full text |Cite
|
Sign up to set email alerts
|

Parental Magma and Emplacement of the Stratiform Uitkomst Complex, South Africa

Abstract: The Uitkomst Complex, a Ni-Cu-PGE-Cr-mineralized layered basic intrusion situated approximately 200 km due east of Pretoria, South Africa, hosts commercially viable magmatic base-metal sulfide deposits. The Complex has a concordant 207 Pb/ 206 Pb zircon age of 2044 ± 8 Ma, suggesting that it is coeval with the Rustenburg Layered Suite (RLS) of the Bushveld Complex. Chemical modeling, using summation and least-squares optimization techniques, provides evidence that the boninitic Bushveld B1 magma is parental to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 19 publications
1
20
0
Order By: Relevance
“…The new U-Pb zircon age for the Uitkomst diorite of 2057.64 ± 0.69 Ma overlaps within uncertainty with a 207 Pb/ 206 Pb baddeleyite age of 2054.5 ± 6.9 Ma from a coarse-grained gabbro, taken from tailings, that likely represents the Main Gabbronorite (Wabo et al 2015) and it is significantly older than the previous U-Pb zircon SHRIMP age of 2044 ± 8 Ma from a diorite also from the Main Gabbronorite (De Waal et al 2001; Fig. 12).…”
Section: Geochronologysupporting
confidence: 53%
See 2 more Smart Citations
“…The new U-Pb zircon age for the Uitkomst diorite of 2057.64 ± 0.69 Ma overlaps within uncertainty with a 207 Pb/ 206 Pb baddeleyite age of 2054.5 ± 6.9 Ma from a coarse-grained gabbro, taken from tailings, that likely represents the Main Gabbronorite (Wabo et al 2015) and it is significantly older than the previous U-Pb zircon SHRIMP age of 2044 ± 8 Ma from a diorite also from the Main Gabbronorite (De Waal et al 2001; Fig. 12).…”
Section: Geochronologysupporting
confidence: 53%
“…However, until recently, this model lacked clear geochronological support. De Waal et al (2001) determined an age of 2044 ± 8 Ma, not overlapping with recent ages for the Bushveld (2055-2056 ± ∼1 Ma, Zeh et al 2015;2056.88 ± 0.41-2057.04 ± 0.55 Ma, Scoates and Wall 2015). The multi-grain baddeleyite age for Uitkomst of Wabo et al (2015, 2054 shows better overlap with the Bushveld event, but still lacks sufficient precision.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Anhaeusser (2004) reflects that although the Trompsburg intrusion could represent a significant exploration target for platinum group metals, the great depth of the intrusion will probably preclude any mineral occurrences being exploited in the foreseeable future. Economic or sub economic Cu-Ni-PGE sulphide ores are also found in some satellite intrusions of Bushveld lineage, notably the Uitkomst Complex (De Waal et al, 2001). Satellite intrusions of the Bushveld Complex (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Molopo Farms, Uitkomst, Roodekraal, Lindequesdrift, Rietfontein etc., Fig. 1) occur up to several hundred km in the periphery of the Bushveld (Anhaeusser, 2004;De Waal et al, 2001;Tankard et al, 1982 andVon Gruenewaldt et al, 1988) which previously led to the thinking that the Trompsburg intrusion constitutes part of the Bushveld igneous Complex (Maier et al, 2003). However, results of a SHRIMP U/Pb isotope study on zircons from two gabbroic samples of the Trompsburg intrusion (Maier et al, 2003) indicated a crystallisation age of 1915 ± 6 Ma.…”
Section: Introductionmentioning
confidence: 99%